Doctor of Public Health-Crisis Management and COVID-19 Prevention and Control: A Case Study in China - Cai, Weiqin; Gao, Runguo; Jing, Qi; Wang, Chunping; Hou, Ningning; Liu, Weide; Gao, Qianqian; Sun, Xiaodong (Frontiers in Public Health, 2022)
In the fields of public health policy and public health care, advanced educational programs are an important strategy in dealing with public health crises. The COVID-19 pandemic has exposed the global need for skilled public health leaders and managers to address complex public health challenges, which requires the strengthening of public health education at the highest levels. This paper is a qualitative case study of a special educational program for doctors of public health in China. The program's educational objectives are in line with epidemic prevention and control. With the goal of developing the world's leading national public health management system, the Chinese government established an advanced academic program for public health crisis management. The program offers doctoral students a multidisciplinary degree based upon the theoretical knowledge of crisis management, supported by advanced training in the foundational concepts, theories, and practices of public health, and the study of basic medicine which provides the theoretical support for developing essential clinical skills. Program graduates develop the theoretical, practical, and leadership-related capabilities required for the management of national emergencies. The program introduced in this paper meets current epidemic prevention and control needs and should be considered by public health policy makers, leaders, and scholars in the discussion of advanced public health policy and health care education in China, including the development of an internationally recognized Doctor of Public Health program.